Study of ISLE-BASED STEM Approaches and Models in Its Use for Teacher Professionalism Development in Geometric Optical Case Studies - Fathiya Nufus; Irwandi Irwandi; Syahrun Nur; Evendi Evendi (Jurnal Penelitian Pendidikan IPA, 2022)
21st century learning emphasizes that information and knowledge are obtained together with good communication and cooperation among fellow students in building their knowledge. One of the appropriate learning models and approaches to be applied in accordance with 21st century learning is the Investigative Science Learning Environment (ISLE) combined with Science, Technology, Engineering and Mathematics (STEM). This study uses the Research and development (R & D) method with the ADDIE (Analysis-Design-Develop-Implement-Evaluate) model. The product developed in this study is ISLE-based STEM learning media in the form of Student Worksheets on Geometry Optics material and the relationship between ISLE-based STEM learning and Teacher Professionalism Development is reviewed